2020
DOI: 10.1088/1742-6596/1618/6/062020
|View full text |Cite
|
Sign up to set email alerts
|

WRF-Simulated Springtime Low-Level Jets over Iowa: Implications for Wind Energy

Abstract: High-resolution simulations with the Weather Research and Forecasting (WRF) model are analyzed to characterize the frequency, intensity, height, and duration of springtime low-level jets (LLJ) and their implications for wind energy resource assessment and planning in Iowa. The time evolution of short-duration LLJ is analyzed to understand wind behavior around LLJ events and to illustrate their importance for high-frequency (few hours) variability in wind speeds and rotor plane turbulent kinetic energy (TKE). D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The regional flow is generally dominated by southeasterly and southwesterly flow in winter and spring and dominated by southwesterly flow in summer [54]. The LLJ is more frequently associated with north/south wind directions and is more common in the northeast of the domain in spring [31] and may account for the high frequency of extreme shear in March and at night.…”
Section: Shear Across the Rotor Planementioning
confidence: 99%
See 1 more Smart Citation
“…The regional flow is generally dominated by southeasterly and southwesterly flow in winter and spring and dominated by southwesterly flow in summer [54]. The LLJ is more frequently associated with north/south wind directions and is more common in the northeast of the domain in spring [31] and may account for the high frequency of extreme shear in March and at night.…”
Section: Shear Across the Rotor Planementioning
confidence: 99%
“…Although LLJ are typically assumed to be centered at heights above 300 m above ground level (a.g.l.) [29], in some locations, these LLJ are located at heights of relevance to wind resources and WT operating conditions (e.g., in the Southern Great Plains [30]), and a recent study has demonstrated their prevalence at WT relevant heights over parts of the Midwest including Iowa during spring [31]. When present, such phenomena may result in very high shear across the rotor plane [30] or complex shear profiles across the rotor-swept area [32].…”
Section: Introductionmentioning
confidence: 99%